Theoretical analysis and numerical simulation of square honeycombs. Issue 1 (February 2021) - Li, Z G; Wang, J M; Li, M; Chen, F Y
Abstract: Aluminum honeycomb is widely used in energy absorption field for its special structure and excellent performance. The three-dimensional finite element models of aluminum honeycombs are developed in order to explore the mechanical behaviors under out-of-plane and in-plane compression. The simulation method is validated based on the experimental results of hexagonal honeycombs. Based on the simplified super folding element theory, we study the platform stress of square honeycomb under out-of-plane and in-plane compression. The theoretical formulas of platform stress under two conditions are provided in this study. Finally, compared with the simulation results of square honeycomb compression, the maximum error between the simulation and the theory for the platform stress under out-of-plane and in-lane compressions is less than 10%, and 15%, respectively. Both the results predicted by the theoretical formulas show high precision.